Evaluation of Selective Harmonic Elimination Pulse Width Modulation Technique for Unipolar Single-Phase H-Bridge Inverter: Comparative Study - Hussain Attia (Institute of Advanced Engineering and Science, 2018)
In this paper, a detailed comparative study about evaluating the single phase inverter performance based on selective harmonic elimination pulse width modulation (SHE PWM) technique is presented. Set of nonlinear equations are derived, four groups of switching angles are calculated using the numerical iterative method of Newton-Raphson. These angles are representing the ideal solutions to eliminate the low order harmonics from inverter output voltage and load current. Inverter effectiveness is evaluated by comparing the performance based on SHE PWM and based on the conventional constant switching frequency PWM (CSF PWM) technique. Same parameters setting is selected with considering the constant switching frequency value for each case separately as equivalent to the number of switching angles. Moreover, different rated load powers are investigated to explain the merit of SHE PWM within high power applications. MATLAB / Simulink simulation results are clearly indicating the priority of the SHE PWM at all groups of calculated angles and at different load power as well.